2023
DOI: 10.1039/d2mh01217k
|View full text |Cite
|
Sign up to set email alerts
|

Volcano relationships and a new activity descriptor of 2D transition metal–Fe layered double hydroxides for efficient oxygen evolution reaction

Abstract: Iron (Fe) sites played a critical role in boosting the catalytic activity of transition metal layered double hydroxides (LDHs) electrocatalysts for oxygen evolution reaction (OER), but the contribution of Fe...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Overall, the n -BuLi treatment successfully introduced O vacancy defects and imparted an amorphous structure to the NiFe-LDH catalysts. As shown in the FT-IR spectrum (Figure S3c), no obvious difference appeared in the C–H peak near 2900 cm –1 between NiFe-LDH and treated NiFe-LDH, indicating that few n -butyl groups remained in the treated NiFe-LDH. , …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, the n -BuLi treatment successfully introduced O vacancy defects and imparted an amorphous structure to the NiFe-LDH catalysts. As shown in the FT-IR spectrum (Figure S3c), no obvious difference appeared in the C–H peak near 2900 cm –1 between NiFe-LDH and treated NiFe-LDH, indicating that few n -butyl groups remained in the treated NiFe-LDH. , …”
Section: Resultsmentioning
confidence: 84%
“…As shown in the FT-IR spectrum (Figure S3c), no obvious difference appeared in the C−H peak near 2900 cm −1 between NiFe-LDH and treated NiFe-LDH, indicating that few n-butyl groups remained in the treated NiFe-LDH. 28,32 The overpotential, Tafel slope, and durability were tested to evaluate the OER properties; the results are shown in Figure 3. The electrocatalysts were tested by using a three-electrode system in the 1 M KOH solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The high OER activity is correlated to the early formation of the low-frequency peaks or the lower potential required for the peaks in the low and intermediate regions. 60 The maximum phase angles of Co MOF/NF, Co 2 P/NF and CoFeP/NF with respect to the applied potential are shown in Fig. 8d.…”
Section: Resultsmentioning
confidence: 99%
“…The results in Figure S13 (Supporting Information) showed that the I D / I G values of Fe–N–C‐ x gradually increased with the content of etching reagent, indicating the increased etching effect and more defects in Fe–N–C‐ x . In our previous study, [ 41 ] we have demonstrated that only a proper defect concentration can lead to the optimal adsorption of intermediates and thus the best catalytic performance, so that the Fe–N–C‐2 sample with appropriate defect concentration could exhibit the best ORR performance. For the purpose of examining the surface chemical states of the produced catalysts, X‐ray photoelectron spectroscopy (XPS) was employed (Figure S14, Supporting Information) and the obtained element contents were listed in Table S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%